The Importance of Financial Condition Indices in South-Eastern Europe - GANCHEV, Gancho Todorov; PASKALEVA, Mariya Georgieva (International Journal of Contemporary Economics and Administrative Sciences, 2020)
In this paper, we construct the Financial Conditions Index of 11 European economies - Bulgaria, Czech Republic, Croatia, Estonia, Hungary, Lithuania, Latvia, Poland, Romania, Germany, and Turkey. We aim to reveal the sensitivity of the FCIs to the dynamics of the global financial conditions and to investigate and establish dependencies between the constructed FCIs and those of the USA and Germany. We prove that FCI is sensitive to the upcoming shocks from the USA and Germany. When studying the sensitivity of the FCIs to the U.S and German indices we prove that the impact of the American conditions is substantially stronger. We may conclude that the tightening of financial conditions causes a slowdown in GDP growth in the future while a weakening stimulates inflation. We proved that local financial conditions incorporate faster and more strongly the influence of global financial shocks than changes in domestic policy rates.